EFFICIENT REGENERATION AND AGROBACTERIUM-MEDIATED TRANSFORMATION PROTOCOL FOR RECALCITRANT INDICA RICE (ORYZA SATIVA L.). - Fook, Clement Wong Kiing; Lai, Kok Song; Wong, Mui Yun; Mahmood, Maziah (Emirates Journal of Food and Agriculture, 2015)
Rice shoot apices have been selected as the potential explant for genetic transformation since lesser time for regeneration and lower incidence of somaclonal variants were reported as compared to embryogenic callus. Utilizing this explant, efficient regeneration and Agrobacterium transformation protocol have been developed for the recalcitrant Malaysian indica rice, MR219. In this study, 4 mg/L of KIN was selected as the suitable cytokinin for multiple shoot formation as compared to TDZ and BAP. KIN was able to produce relatively high number of shoots as well as producing good quality shoots with the highest total chlorophyll content, and moderately high total soluble sugar content. In-vitro shoots were successfully acclimatized in glasshouse without signs of infertility. The optimization of the Agrobacterium-mediated protocols revealed that Agrobacterium supervirulent strain EHA101, shoot apices derived from 4 days old seedlings, excised wounded explants, 30 minutes of bacterial immersion time and 72 hours (3 days) of co-cultivation gave the highest percentage of plant transiently expressing two reporter genes – GFP and GUS. After 30 days of hygromycin selection and PCR verification of the putative transformants, the transformation efficiency was reported to be 5.83%. The established regeneration system and transformation protocol for MR219 rice shoot apices will serve as an essential fundamental platform for the production of transgenic rice with superior traits.